Highly thermally stable cyclotriphosphazene based perfluoropolyether lubricant oil. (October 2015) - Wang, Xiaobai; Tan, Angeline Yan Xuan; Cho, Ching Mui; Ye, Qun; He, Chaobin; Ji, Rong; Xie, Hui Qing; Tsai, Jack Wen Huei; Xu, Jianwei
Abstract: Novel cyclotriphosphazene based lubricant oil (Lube-PN ) for heat-assisted magnetic recording media was synthesized by reacting hexachlorocyclotriphosphazene with pentafluorophenol, followed by treatment with a hydroxy-terminated perfluoropolyether in a high yield. Its chemical structure was confirmed by 1 H and 31 P NMR. Its properties including viscosity, thermal stability, tribology, laser resistance as well as mobility behaviour on the hard disk surface were investigated. The thermal properties of Lube-PN were analysed using thermogravimetric analysis, and the thermal aging results showed that the about 80% of Lube-PN was retained even after heating at 300 °C for 8 h. The Lube-PN also exhibited comparable bonding ratio, friction coefficient, moderate mobility and better laser resistance than commercial perfluoropolyether based lubricant oils. Highlights: A new cyclotriphosphazene-based PFPE lubricant is synthesized. Lubricant shows exceptional long-term thermal stability. Lubricant exhibits better laser resistance than commercial PFPE lubricants. Lubricant shows outstanding tribology properties.